Synthesis of 5-(Aryl)amino-1,2,3-triazole-containing 2,1,3-Benzothiadiazoles via Azide–Nitrile Cycloaddition Followed by Buchwald–Hartwig Reaction - Pavel S. Gribanov; Anna N. Philippova; Maxim A. Topchiy; Dmitry A. Lypenko; Artem V. Dmitriev; Sergey D. Tokarev; Alexander F. Smol’yakov; Alexey N. Rodionov; Andrey F. Asachenko; Sergey N. Osipov (Molecules, 2024)
An efficient access to the novel 5-(aryl)amino-1,2,3-triazole-containing 2,1,3-benzothiadiazole derivatives has been developed. The method is based on 1,3-dipolar azide–nitrile cycloaddition followed by Buchwald–Hartwig cross-coupling to afford the corresponding N-aryl and N,N-diaryl substituted 5-amino-1,2,3-triazolyl 2,1,3-benzothiadiazoles under NHC-Pd catalysis. The one-pot diarylative Pd-catalyzed heterocyclization opens the straightforward route to triazole-linked carbazole-benzothiadiazole D-A systems. The optical and electrochemical properties of the compound obtained were investigated to estimate their potential application as emissive layers in OLED devises. The quantum yield of photoluminescence (PLQY) of the synthesized D-A derivatives depends to a large extent on electron-donating strengths of donor (D) component, reaching in some cases the values closed to 100%. Based on the most photoactive derivative and wide bandgap host material mCP, a light-emitting layer of OLED was made. The device showed a maximum brightness of 8000 cd/m2 at an applied voltage of 18 V. The maximum current efficiency of the device reaches a value of 3.29 cd/A.